Data structures with abstract data types and ADA - Daniel F Stubbs (PWS, 1993)
The central topics of this book are the classical data structures of computer science and the basic algorithms for manipulating those data structures. The progrmming language ADA is used in the book to both specify and implement the data structures. The book is organized around the basic structures of computer science: sets, lists, trees, and networks or graphs